2023
DOI: 10.1200/go.22.00384
|View full text |Cite
|
Sign up to set email alerts
|

QPOLE: A Quick, Simple, and Cheap Alternative for POLE Sequencing in Endometrial Cancer by Multiplex Genotyping Quantitative Polymerase Chain Reaction

Abstract: PURPOSE Detection of 11 pathogenic variants in the POLE gene in endometrial cancer (EC) is critically important to identify women with a good prognosis and reduce overtreatment. Currently, POLE status is determined by DNA sequencing, which can be expensive, relatively time-consuming, and unavailable in hospitals without specialized equipment and personnel. This may hamper the implementation of POLE-testing in clinical practice. To overcome this, we developed and validated a rapid, low-cost POLE hotspot test by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Tian et al showed that P286R and V411L variants are associated with higher a Pol ε activity than POLEwt [90]. [23,24,86,92]. Sanger sequencing preferentially amplifies the normal sequence of the POLE gene.…”
Section: Polemutmentioning
confidence: 99%
See 2 more Smart Citations
“…Tian et al showed that P286R and V411L variants are associated with higher a Pol ε activity than POLEwt [90]. [23,24,86,92]. Sanger sequencing preferentially amplifies the normal sequence of the POLE gene.…”
Section: Polemutmentioning
confidence: 99%
“…However, during the analysis of 359 cases, McAlpine et al identified most (82%) POLE mutations as being pathogenic [ 85 ]. The most frequent pathogenic mutations of POLE are located in 11 loci across 9, 11, 13, and 14 exons [ 86 ]. Among them, substitutions P286R, V411L, S297F, A456P, and S459F were indicated by León-Castillo et al as being the most commonly occurring, while mutations in the six remaining domains (i.e., M295R, F367S, D368Y, L424I, P436R, and M444K) were rarer [ 86 , 87 ] ( Table 1 ).…”
Section: Molecular Classification Of Endometrial Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this, Van den Heerik et al crafted a solution to this issue by developing QPOLE, a POLE hotspot test that is both quick, taking approximately 2 h, and cost-effective. The test uses a quantitative polymerase chain reaction (qPCR) assay [ 68 ]. This methodology stands out as an efficient and accurate testing procedure for POLE in endometrial biopsy and hysterectomy specimens.…”
Section: Integrating Molecular Classifications Into Figo 2023 Staging...mentioning
confidence: 99%
“…14,24,25 Other groups have published on cost-effective and efficient approaches for POLE sequencing, which can be utilized in the molecular work-up of ECs. [26][27][28][29] These F I G U R E 1 Schematic of the molecular subtype classification of endometrial carcinoma using surrogates based on immunohistochemistry and/or molecular data. The distribution of histological types by molecular subtype are obtained from Rios-Doria et al 14 Abn, abnormal; CN-H, copy number-high; CN-L, copy number-low; ED, exonuclease domain; IHC, immunohistochemistry; MMR, mismatch repair; MSI-H, microsatellite instability-high; NGS, next generation sequencing; NSMP, no specific molecular profile; POLE, polymerase epsilon.…”
Section: Molecular Subtypes Of Ec: the Beginning And Implementation I...mentioning
confidence: 99%